Detecting an inclusion in an elastic body with residual stress. (April 2018) - Lin, Chia-Hung
Abstract: We consider the inverse problem for estimating the size of an inclusion D, D ⊂ Ω, in an elastic body with residual stress. The constitutive equation of this elasticity system is not isotropic, due to the presence of residual stresses. We prove that the size of the inclusion can be estimated both from above and below by using only one pair of traction–displacement measurement on the boundary of Ω .